Risk of fall among the hospitalized over-49 population. A retrospective cohort study in a hospital. (13th November 2019) - Gilardi, F; Mariani, T; Liotta, G; Musolino, M; Caredda, E; Morciano, L; Giliberti, C; Morbidelli, S; Lucaroni, F
Abstract: Background: Despite the copious efforts made to prevent the problem, inpatient falls remain one of the most common adverse events in hospitals, with high risks in term of morbidity and mortality rates, as well as high costs for the healthcare system. This study aims to evaluate the inpatient falls incidence rate in a hospital in Rome, Italy. Methods: A retrospective cohort study has been set out based on data collected by a Risk Management Unit concerning the falls of patients over 49 years, which happened in the hospital between 1st July 2008 and 30th June 2013. Data collected from the incident report forms were inserted in a database and analyzed using the statistical program SPSS, 20.0 Illinois version. Results: During the period observed, 516 falls were reported. Patients who fell had a mean age of 68.8 years (SD ± 16.2). The falls are distributed for these age groups: 109 (21.1%) in 50-64; 129 (25%) in 65-74; 181 (35.1%) in 75-84; 97 (18.8%) in > 84. Fall incidence rate was calculated on the overall number of hospital admissions in the observed period (N = 35, 812) (1.44 per 100 hospital admissions IC95% 1.32-1.56). Most of the patients were men (333; 64.5%) and older than 75 (53.9%). Inpatient falls were more frequent in the medicine wards (incidence rate 2.2 per 100 hospital admissions, IC95% 1.85-2.55, ). The 51.6% of falls happened during the night shift. Severe outcome resulted in 13.6% of falls. Most of the falls (52.3%) happened within three days from the hospital admission. At multivariate analysis, a period of 2-3 days from hospital admission is the main risk factor to determine severe outcomes such as death or cranial trauma (p = 0.02; OR 2.87 IC95% 1.16-7.09). Conclusions: The study contributes to measure the phenomenon in older adults and age group 50-64, identifying a specific indicator to properly measure inpatient falls incidence rate in the elderly. The study gives indications on the main risk factors related to this adverse event and on prevention strategies. Key messages: Falls in hospital is an important adverse event not only in the elderly. The first period of three days from the hospital admission constitutes the main risk factor for the falls.